2019
DOI: 10.1038/s41598-018-36624-5
|View full text |Cite
|
Sign up to set email alerts
|

The proteome of frozen-thawed pig spermatozoa is dependent on the ejaculate fraction source

Abstract: The preservation of sperm functional parameters and fertility post-cryopreservation largely varies in the porcine, a species with a fractionated ejaculate. Although intrinsic individual differences have primarily been linked to this variation, differences in protein abundance among frozen-thawed (FT)-spermatozoa are far more relevant. This study, performed in two experiments, looked for proteomic quantitative differences between FT-sperm samples differing in post-thaw viability, motility, apoptosis, membrane l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 61 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…Protein extraction of sperm samples was conducted as described previously by Perez-Patiño et al [50]. Briefly, sperm samples were centrifuged (14,000× g for 10 min; Eppendorf 5424R, Eppendorf AG, Hamburg, Germany) and the total protein of the resulting sperm pellets were extracted using UTC buffer (7 M Urea, 2 M thiourea, 4% 3-((3-cholamidopropyl) dimethylammonio)-1-propanesulfonate (CHAPS)), supplemented with protease inhibitor cocktail (1%, v / v ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein extraction of sperm samples was conducted as described previously by Perez-Patiño et al [50]. Briefly, sperm samples were centrifuged (14,000× g for 10 min; Eppendorf 5424R, Eppendorf AG, Hamburg, Germany) and the total protein of the resulting sperm pellets were extracted using UTC buffer (7 M Urea, 2 M thiourea, 4% 3-((3-cholamidopropyl) dimethylammonio)-1-propanesulfonate (CHAPS)), supplemented with protease inhibitor cocktail (1%, v / v ).…”
Section: Methodsmentioning
confidence: 99%
“…A SWATH analysis was performed by liquid chromatography (LC) using a NanoLC Ultra 1D plus Eksigent (Eksigent Technologies, Dublin, CA, USA) connected to an AB SCIEX TripleTOF 5600 mass spectrometer (AB SCIEX, Framingham, MA, USA) in direct injection mode following the procedure described by Perez-Patiño et al [50]. Firstly, for the spectral library acquisition, 5 µL of a mixture of the twelve digested samples (2 µL per sample) was loaded on a trap NanoLC precolumn (3-μm particle size C18-CL, 350 µm diameter × 0.5 mm long; Eksigent Technologies, Dublin, CA, USA) and desalted with 0.1% TFA at 3 µL/min for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that absence or weak expression of AKAP3 and AKAP4 has been described over the years as being related to sperm dysfunctions with motility impairments (Miki et al, 2002;Hillman et al, 2013;Xu et al, 2020). In contrast, the upregulation of either AKAP4 or AKAP3 in frozen-thawed boar sperm might be associated with their premature capacitation (Chen et al, 2014;Perez-Patino et al, 2019b). A higher expression of AKAP3 and AKAP4 in Duroc boar sperm might promote the sperm function; they play a crucial role in sperm motility.…”
Section: Sperm Proteome Differences Between Yorkshire and Duroc Boarmentioning
confidence: 99%
“…In-depth proteomic analyses of boar spermatozoa have been performed using shotgun and gel-based methods [6]. The proteome of pig spermatozoa is remodeled during ejaculation [7]. The comparative proteomes of prenatal muscle tissues among TP, Wujin pigs and large White pigs have been analyzed using the isobaric tag for relative and absolute quantification (iTRAQ) [8].…”
Section: Introductionmentioning
confidence: 99%